Influence of the geometrical characteristics of the surface with spherical wells on heat exchange of water and air - Dubrovskyi V.V.; Pidvysotskyi O.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2015)
One of the ways of increasing the cooling capacity of film-type cooling towers is the use of sprinklers in the form of profiled surfaces with spherical dimples, which provide a high efficiency of heat transfer from water to air. The search for new shapes of sprinkler surfaces, which can enhance the efficiency of the operation of cooling towers, is an important scientific and technical problem.The aim of the present work is to advance the geometric characteristics of sprinkler surfaces, namely, to study experimentally the influence of the depth of spherical dimples and the density of their position on the surface on heat transfer from water to air as well as to propose efficient profiled sprinkler surfaces for film-type cooling towers.Experiments were carried out under different conditions of interaction between the phases water – air at transverse blow of the liquid film by air having different velocities, and also in quiescent air.We found profiled surface that takes into account the assemblage of such factors as the sizes of spherical dimples, their depth, and distance between neighboring dimples and, hence provides the most efficient heat transfer. Such surface can be used as a sprinkler for film-type cooling towers.